Online banking adoption among academicians at MTUN Universities in Malaysia - Al-Subari, Saleh Nasser (2017)
The advancement of technology especially the invention of the internet has changed the way organizations conduct their businesses today including banks especially in offering online banking services. Online banking services had been introduced in Malaysia in the year 2000. However, bank customers including academicians in Malaysia are influenced by issues of trust of online banking which also affects their level of adoption. In addition, there were only few studies which have combined Technology Acceptance Model (TAM) and Perceived Risk Theory (PRT) in understanding the adoption of online banking services in Malaysia. Therefore, this study intended to determine the factors influencing the adoption of online banking based on TAM (Perceived Usefulness, PU; Perceived Ease of Use, PEOU) as the base model, with Government Support (GS) being included as the additional variable. Furthermore, based on PRT, Trust is also included in this study. Variables influencing Trust (Perceived Security, PS; Perceived Risk, PR; Perceived Privacy, PP) are also assessed as well as the moderating influence of Trust on the relationship between PU, PEOU and GS, with the adoption of online banking in Malaysia. Respondents of this study were selected among academicians at Malaysian Technical Universities Network (MTUN) based on simple random sampling approach. Data was collected through the use of survey questionnaires. A total of 600 questionnaires were distributed while 253 of them were retrieved and usable for data analysis. Data analysis was carried out with the aid of the Statistical Package for Social Sciences (SPSS). The main results of this study revealed that PU and PEOU have significant influence on the adoption of online banking while GS was found not to be significant. Besides, PS and PR were also found to be significant in influencing Trust, while PP was found to be non-significant. Finally, Trust is also found to have a moderating influence on the relationship between PU and GS with the adoption of online banking and not significant in moderating the relationship between PEOU with the adoption of online banking. These findings sheds some valuable information to be considered by banks in offering online banking services to their customers as well as additional new practical and informational understanding to current literature on the adoption of online banking services.